The logic of the nation: Nationalism, formal logic, and interwar Poland - David E. Dunning (Studia Historiae Scientiarum)
Between the World Wars, a robust research community emerged in the nascent discipline of mathematical logic in Warsaw. Logic in Warsaw grew out of overlapping imperial legacies, launched mainly by Polish-speaking scholars who had trained in Habsburg universities and had come during the First World War to the University of Warsaw, an institution controlled until recently by Russia and reconstructed as Polish under the auspices of German occupation. The intellectuals who formed the Warsaw School of Logic embraced a patriotic Polish identity. Competitive nationalist attitudes were common among interwar scientists – a stance historians have called “Olympic internationalism,” in which nationalism and internationalism interacted as complementary rather than conflicting impulses.